Streptococcus suis 2 Transcriptional Regulator TstS Stimulates Cytokine Production and Bacteremia to Promote Streptococcal Toxic Shock-Like Syndrome - Xu, Zhongmin; Chen, Bo; Zhang, Qiang; Liu, Liang; Zhang, Anding; Yang, Yujie; Huang, Kaisong; Yan, Shuxian; Yu, Junping; Sun, Xiaomei; Jin, Meilin (Frontiers in Microbiology, 2018)
Two large-scale outbreaks of streptococcal toxic shock-like syndrome (STSLS) have revealed Streptococcus suis 2 to be a severe and evolving human pathogen. We investigated the mechanism by which S. suis 2 causes STSLS. The transcript abundance of the transcriptional regulator gene tstS was found to be upregulated during experimental infection. Compared with the wild-type 05ZY strain, a tstS deletion mutant (∆tstS) elicited reduced cytokine secretion in macrophages. In a murine infection model, tstS deletion resulted in decreased virulence and bacterial load, and affected cytokine production. Moreover, TstS expression in the P1/7 strain of S. suis led to the induction of STSLS in the infected mice. This is noteworthy because, although it is virulent, the P1/7 strain does not normally induce STSLS. Through a microarray-based comparative transcriptomics analysis, we found that TstS regulates multiple metabolism-related genes and several virulence-related genes associated with immune evasion.